2021
DOI: 10.1371/journal.pone.0261185
|View full text |Cite
|
Sign up to set email alerts
|

Why big brains? A comparison of models for both primate and carnivore brain size evolution

Abstract: Despite decades of research, much uncertainty remains regarding the selection pressures responsible for brain size variation. Whilst the influential social brain hypothesis once garnered extensive support, more recent studies have failed to find support for a link between brain size and sociality. Instead, it appears there is now substantial evidence suggesting ecology better predicts brain size in both primates and carnivores. Here, different models of brain evolution were tested, and the relative importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 120 publications
1
6
1
Order By: Relevance
“…Encephalisation in carnivoran species is positively associated with the average size of the home range. Consistently with previous studies on mammalian taxa 80 – 84 , this result is in adequation with the Cognitive Buffer Hypothesis (CBH) and could be explained by the fact that a larger brain may constitute a selective advantage for species that need to memorize a large amount of temporal and geographic information 37 , 85 . Indeed, the ability to use mental representation of the surrounding environment and to memorize the food distribution is very important as it impacts the foraging success 86 88 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Encephalisation in carnivoran species is positively associated with the average size of the home range. Consistently with previous studies on mammalian taxa 80 – 84 , this result is in adequation with the Cognitive Buffer Hypothesis (CBH) and could be explained by the fact that a larger brain may constitute a selective advantage for species that need to memorize a large amount of temporal and geographic information 37 , 85 . Indeed, the ability to use mental representation of the surrounding environment and to memorize the food distribution is very important as it impacts the foraging success 86 88 .…”
Section: Discussionsupporting
confidence: 90%
“…However, this study was based on a relatively small sample size (i.e., 36 species) due to technical difficulties in acquiring images from CT-scanning. We therefore suggest that this restricted sample size was possibly not sufficient to highlight the correlation that we and other studies 82 , 84 found between the relative brain size and the home range. In the future, additional research on the endocranial shape will be necessary to assess whether the increase in the parietal cortex for species with a large home range may be responsible for the increase in the overall size of the brain.…”
Section: Discussioncontrasting
confidence: 62%
“…Numerous studies have addressed the mechanisms underlying the evolution of cognitive abilities in primates, using brain size as a proxy (Powell, Isler et al 2017, Chambers, Heldstab et al 2021, van Schaik, Triki et al 2021, DeCasien, Barton et al 2022). One of the major hypotheses, referred to as the 'social brain' hypothesis, proposes that social interactions require higher cognitive skills such that the complexity of social interactions played a central role in the increase in brain size during primate evolution (Dunbar 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the Ecological Intelligence Hypothesis (EIH) and its variants emphasise informational challenges posed by ecological variables, such as changeable food sources and climatic conditions [2,8,[12][13][14][15]. A large body of research has investigated social and ecological correlates of brain size across a range of taxa, including primates, ungulates, carnivores and birds [3,[16][17][18][19][20][21][22][23][24][25][26][27][28]. However, results are often inconsistent and contradictory [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…[16,21]) variables associated with the competing hypothesis. However, the combination of variables is known to have a substantial influence on the results of primate and carnivora brain size models [27,32]. In addition, where covariates are sourced from can have a substantial impact on results.…”
Section: Introductionmentioning
confidence: 99%